Some problems of biochemistry in anthropology - Woszczyk, Jerzy (Anthropological Review, 1974)
An attempt has been made to estimate the value of attributes of biochemistry for anthropology. Difficulties were pointed out in calculating the correct values (standards) for population in connection with inborn. genetically conditioned defects of metabolism. Three groups of agents which influence the size of biochemical parameters were treated only in a very general way. They are the genetic intraand extra-constitutional agents. To examine the problem of so-called biological norm the population of enlisted men (n=314) was used, for whom the level of ceruloplasmine in their blood serum was fixed. The obtained empiric decomposition was compared with the theoretically normal one. The two decompositions show some differences. The extent of these differences is calculated in test χ2. In evaluating the type of ceruloplasmin decomposition in the population of recruited men attention was paid to the rare, almost exceptional unity in occurrence of decompositions: of the empiric and the theoretically normal one.